2013
DOI: 10.1080/10503307.2012.735775
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapists' self-reports of their interpersonal functioning and difficulties in practice as predictors of patient outcome

Abstract: The need for psychotherapy research to understand the therapist effect has been emphasized in several studies. In a large naturalistic study (255 patients, 70 therapists), this topic was addressed using therapists' self-assessed difficulties in practice and interpersonal functioning in therapeutic work as predictors of patient outcome in three conventional outcome measures. Three-level growth curve analyses were employed to assess whether the therapist characteristics, measured by the Development of Psychother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 65 publications
4
73
1
6
Order By: Relevance
“…For reasons of better comparability between the two perspectives, we applied the factor structure from the therapist perspective on both perspectives. All variables were centred to the mean, which has been recommended as a helpful device in the interpretation of the results and in the reduction of multicollinearity by several authors (Heck et al, 2010;Hox, 2010;Nissen-Lie, Monsen, Ulleberg, & Rønnestad, 2013). We applied the MLM in line with the recommendations of Heck, Thomas, and Tabata (2010) and Field (2009).…”
Section: Multilevel Modellingmentioning
confidence: 99%
“…For reasons of better comparability between the two perspectives, we applied the factor structure from the therapist perspective on both perspectives. All variables were centred to the mean, which has been recommended as a helpful device in the interpretation of the results and in the reduction of multicollinearity by several authors (Heck et al, 2010;Hox, 2010;Nissen-Lie, Monsen, Ulleberg, & Rønnestad, 2013). We applied the MLM in line with the recommendations of Heck, Thomas, and Tabata (2010) and Field (2009).…”
Section: Multilevel Modellingmentioning
confidence: 99%
“…That situation has changed substantially, with evidence that some of our emotional states are associated with therapy processes and outcomes. At a general level, Westra, Aviram, Connors & Kertes (2012) and Nissen-Lie, Monsen, Ulleberg & Rønnestad (2013) have shown that our emotional reactions to patients can facilitate or hinder therapy. For example, Beutler, Crago & Arizmendi (1986) have concluded that therapists who are lower in emotional disturbance have more consistent patient outcomes.…”
Section: Our Emotionsmentioning
confidence: 99%
“…In one influential study, Nissen-Lie et al (2013) found that the most successful therapists in their sample were also the ones who exhibited the most professional self-doubt. Within the case of Mr. R, professional self-doubt runs like a constant thread through the self-description of the author.…”
Section: Discussionmentioning
confidence: 99%